ANALISIS KETERAMPILAN PROSES SAINS SISWA SEKOLAH DASAR PADA MUATAN MATERI IPA DI SDN 066652 MEDAN - NINGSIH, YAZIMA FADILA; JUNITA, EVI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
This research aims to determine basic abilities in science process skills in science material at SDN 066652 Medan. The research method uses a qualitative approach in descriptive form as a basis for investigating the implementation of students' science process skills at SDN 066652 Medan. Through interviews and direct observation, the research subject, namely the sixth grade teacher, of the science learning process carried out by the teacher in class, as well as documentation in the form of tools to support the implementation of learning with science process skills. Data analysis was carried out using descriptive analysis techniques which included data reduction to identify emerging patterns or themes, presenting the data in the form of tables and relevant narratives and finally drawing conclusions based on the findings resulting from the analysis. The results of qualitative research data analysis show that sixth grade elementary school students apply basic science process skills when learning science in every aspect except the communicating aspect. It was also found that there were differences in the application of science process skills between male and female students. The results of the research concluded that students at SDN 06652 Medan have basic abilities in science process skills in science content with differences in ability between male and female students which is one of the obstacles in implementing science process skills in addition to the obstacles of differences in the cognitive level of each student, time management and procurement of practical equipment, as well as difficulties in determining the right learning design. It is hoped that this research can make a positive contribution in developing more effective abilities in applying science process skills to science learning in elementary schools. ABSTRAKPenelitian ini bertujuan untuk mengetahui kemampuan dasar pada keterampilan proses sains pada muatan materi IPA di SDN 066652 Medan. Metode penelitian menggunakan pendekatan kualitatif dalam bentuk deskriptif sebagai landasan untuk menyelidiki implementasi keterampilan proses sains siswa di SDN 066652 Medan. Melalui wawancara dan observasi langsung subjek penelitian yakni guru kelas VI terhadap proses pembelajaran IPA yang dilakukan oleh guru di kelas, serta dokumentasi berupa perangkat pendukung pelaksanaan pembelajaran dengan keterampilan proses sains. Analisis data dilakukan dengan menggunakan teknik analisis deskriptif yang meliputi reduksi data untuk mengidentifikasi pola atau tema yang muncul, penyajian data dalam bentuk tabel dan narasi yang relevan dan terakhir pengambilan kesimpulan berdasarkan temuan yang dihasilkan dari analisis tersebut. Hasil analisis data kualitatif penelitian menunjukkan bahwa siswa kelas VI SD menerapkan kemampuan dasar keterampilan proses sains pada saat pembelajaran IPA pada setiap aspek kecuali pada aspek mengomunikasikan. Ditemukan pula perbedaan penerapan keterampilan proses sains pada siswa laki-laki dan perempuan. Hasil penelitian menyimpulkan bahwa siswa SDN 06652 Medan memiliki kemampuan dasar keterampilan proses sains pada muatan materi IPA dengan perbedaan kemampuan antara siswa laki-laki dengan siswa perempuan yang merupakan salah satu kendala dalam penerapan keterampilan proses sains selain kendala perbedaan tingkat kongnitif setiap peserta didik, manajemen waktu dan pengadaan peralatan praktikum, serta kesulitan menentukan desain pembelajaran yang tepat. Penelitian ini diharapkan dapat memberikan kontribusi positif dalam pengembangan kemampuan yang lebih efektif dalam menerapkan keterampilan proses sains kedalam pembelajaran IPA di sekolah dasar.